Specific test to Canoe Polo - Fernando Alacid Cárceles; Gema Torres Luque (FEADEF, 2009)
The creation of specific test or batteries of test are contributing to increase the knowledge of the sportsmen/women and to achieve the maximum sports performance. From the analysis of the characteristics of a sport like canoe polo, the aim of this paper is to propose a battery of test for canoe polo, as well as the method to carry out it. The battery of test is composed by the following test: throwing a ball of 3 kg; 15 m test; 5 x 10 m test; 20 x 20 m test; and finally driving in zigzag.